The Tourism Potential of Kavala City (Greece) - (:unkn) unknown (MARMARA UNIV, 2017)
Kavala's location on the carriage way between Istanbul and Selanik, its castle and harbour makes Kavala an important city. Kavala has a potential of tourism thanks to its natural attractions as well as its historical and cultural wealth from history to present. Kavala is a center that has appropriate climate to buoy from May to the end of October and in addition to its coasts close to the city, this region provides tourists lots of aquatic sports and any other sport activities such as equestrianism, parkour, climbing. This city's old downtown hosts, mostly in summer, variety of cultural activities such as Phillipi, wood water, international cosmopolis etc and in these festivals, nations stage their own traditional dance performances, music groups and also they exhibit their national cuisines. Kavala has remarkable historical heritages, including not only Philippi archaeological area where historical artifacts are found, remained from Ancient Age, Hellenistic and Rome periods, but castle, museums, churches as well. Even if most of ottoman artifacts offer service out of its fundamental existence, some of them are reserved such as aqueduct, built in Suleyman the magnificient period, Kavalali Mehmet Ali Pasha complex, and finally Ibrahim and Halil Bey (Sir Ibrahim and Halil) mosques.
Keywords: Kavala; tourism; natural attractiveness; historical and cultural monument